Heart-type fatty acid-binding protein may exclude acute myocardial infarction on admission to emergency department for chest pain. (December 2013) - Cappellini, Fabrizio; Da Molin, Simona; Signorini, Stefano; Avanzini, Fausto; Saltafossi, Donata; Falbo, Rosanna; Brambilla, Paolo
Abstract Chest pain is one of the most frequent reasons for presentation to the emergency department (ED), although the estimated prevalence of AMI (acute myocardial infarction) in the ED is about 4%. One criterion for diagnosis of AMI is the demonstration of a rise and/or fall in cardiac troponins, but time is needed for this to happen. Thus, the use of an additional 'early marker' of cardiac injury may aid to exclude AMI rapidly. The aim of the study was to evaluate the possibility of excluding AMI with the determination of heart-type fatty acid-binding protein (H-FABP) on baseline samples of patients referring to the ED for chest pain. 26 AMI patients and 41 non-AMI comparisons were included in the study. Both H-FABP and high sensitivity cardiac troponin T (hs-cTnT) were measured in baseline samples from these subjects. H-FABP had a negative predictive value of 100%, thus indicating the possibility of its usage in a rule-out strategy for AMI in ED for patients presenting with chest pain.